127. Urinary Tract Infection Incidence Is Associated with Recent Environmental Temperatures. (26th November 2018) - Simmering, Jacob; Sewell, Daniel; Polgreen, Linnea; Polgreen, Philip M
Abstract: Background: Urinary tract infections (UTI) are one of the most common infections and the incidence of UTIs is seasonal, peaking in summer months. Relative to other times of the year, incidence of UTIs during the June to September period is approximately 10% greater. Prior work has suggested that a cause of this seasonality may be warmer temperatures during summer months. However, this work focused on inpatients and used average monthly temperatures. Methods: We identified all UTI cases located in 1 of 397 metropolitan statistical areas (MSA) in the contiguous United States between 2011 and 2016 using the Truven Health MarketScan databases. A total of 192 million person-years of data were included in this dataset and a total of 21, 975, 244 outpatient claims for UTI were identified by ICD-9 (599.0) and ICD-10 (N39.0) codes. Weather data for each MSA and date were obtained from the National Centers for Environmental Information. We computed the mean temperature during the period 3 to 8 days prior to the service date of the claim. A Poisson generalized linear model was used to estimate the effect of temperature on the count of UTI cases adjusted for MSA size, day-of-week, and week-of-year. Results: The effect of temperature on UTI risk was significant (likelihood ratio test P < 0.0001). Relative to times when the average temperature 3–8 days prior was 40.1–45°F, UTI incidence exhibited a dose–response relationship as shown in the figure. Conclusion: Incidence of UTIs exhibits a dose–response pattern with temperature during the period 3–8 days prior to presentation. This pattern persists after adjustment for seasonal factors. These results suggest a causal relationship between warm weather, and UTI risk may exist and warrants further investigation. Disclosures: All authors: No reported disclosures.